(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Russian Russian and Uzbek pseudonyms and their place among other types of anthroponyms and in the field of Russian and Uzbek anthroponymy are considered in the article, the history of the formation of names and pseudonyms is analyzed. Classification of pseudonyms depending on the profession, methods and models of formation of pseudonyms. Russian and Uzbek pseudonyms. Literary, stage and political Russian pseudonyms of the XVIII–XXI centuries and Uzbek pseudonyms of the XV–XXI centuries.